2011
DOI: 10.1681/asn.2010080894
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Fibroblast Growth Factor 23 is a Risk Factor for Kidney Transplant Loss and Mortality

Abstract: An increased circulating level of fibroblast growth factor 23 (FGF23) is an independent risk factor for mortality, cardiovascular disease, and progression of chronic kidney disease (CKD), but its role in transplant allograft and patient survival is unknown. We tested the hypothesis that increased FGF23 is an independent risk factor for all-cause mortality and allograft loss in a prospective cohort of 984 stable kidney transplant recipients. At enrollment, estimated GFR (eGFR) was 51 Ϯ 21 ml/min per 1.73 m 2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
214
3
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(240 citation statements)
references
References 46 publications
18
214
3
5
Order By: Relevance
“…These data, support recent experimental evidence pointing to interactions between calcium and phosphorus in the regulation of FGF-23 production (50,51). Because increases of FGF-23 in renal transplant patients have been correlated with both poor graft function and patient survival (52), it is reassuring that levels remained low.…”
Section: Evenepoel Et Alsupporting
confidence: 83%
“…These data, support recent experimental evidence pointing to interactions between calcium and phosphorus in the regulation of FGF-23 production (50,51). Because increases of FGF-23 in renal transplant patients have been correlated with both poor graft function and patient survival (52), it is reassuring that levels remained low.…”
Section: Evenepoel Et Alsupporting
confidence: 83%
“…2,5 Several cohort studies have examined the relationship between FGF-23 and renal outcomes. [10][11][12][13][14][15] In line with findings in the Chronic Renal Insufficiency Cohort cohort 11 and in the MMKD study 10 from analyses not considering the FGF-23-ADMA interaction, we confirmed that the FGF-23-CKD progression relationship was independent of (1) classic risk factors and (2) CKD-specific risk factors, such as proteinuria and the GFR, that are known to belong to the strongest predictors of CKD progression, as well as (3) major biomarkers of CKD mineral and bone disorder, including serum phosphate, 1,25(OH) 2 D, and PTH. These results further highlight the potential relevance of FGF-23 as a novel risk factor for evolution toward kidney failure in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…in the United States, [11][12][13][14] as well as a large study in transplant recipients in Hungary, 15 have coherently associated high plasma FGF-23 with CKD progression toward kidney failure.…”
mentioning
confidence: 91%
“…"MBD" is associated with increased morbidity and mortality in KTRs and also associated with accelerated progression of kidney disease in these patients (19). Nephrocalcinosis, a potential clinical implication of persistent HPT, may be the major cause of disordered mineral metabolism that impaired graft survival (20).…”
Section: Patient and Allograft Survivalmentioning
confidence: 99%